The Importance of Coase Theorem in the Context of Ecological Taxation: Case of Central Asian Region - Rakhimov Afzalbek Kudrat ogly (Scientific Trends, 2023)
In this article, an attempt was made to evaluate the economic and theoretical aspects of the Coase theorem, an analysis of its mechanisms for taxation of the result of environmental losses, the procedure for its application to prevent negative environmental situations, and the impact on the economy of developing countries. The problems were studied by applying Coase's theorem, and scientifically based conclusions and suggestions were given accordingly.
Keywords: economy, ecology, product, competitiveness, theorem, information, resource, government, taxation, pollution, law, efficiency, negotiations.